The Role of Employee Participation and Resistance in the Success of Change Management - Filep, Roland; Ujhelyi, Mária (International Journal of Engineering and Management Sciences, 2022)
Successful change in the lives of organizations has played a particularly important role in the recent turbulently changing decades, and leadership-follower relationships need to be addressed in order to maintain performance. Participation should be ensured for members of the organization and emerging resistance should be addressed. The subject of my research was to examine whether the assessment of the success of change is influenced by the provision of opportunities for employees to make suggestions and their opposition to change. By performing chi-square tests, I came to the conclusion that if the opinion of the worker is heard, they are more likely to judge the change to be successful, however, the manager is not affected by the involvement of the employees in this. However, there is a correlation between employees' resentment to change and the success of change, both from the employee and managerial side, change is more unsuccessful if resentment develops. Based on the results, both factors are important. It is worth drawing the attention of managers to the need to ensure participation, as failure to do so can lead to dissatisfaction among employees, which can also have a negative impact on the success of the organization.